PENGARUH EFIKASI DIRI (SELF EFFICACY) DAN PEMANFAATAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI SISWA KELAS XI MAS NURUSSA’ADAH TEBO - Arpizal Arpizal; Novia Sri Dwijayanti; Zuhri Saputra Hutabarat (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this study was to determine how much influence Self Efficacy and Utilization of Learning Facilities had on the Accounting Learning Outcomes of Class XI Students Mas Nurussa'adah Tebo. This research is included in quantitative research. The method used in this research is the ex-post facto method. Data collection techniques in the form of questionnaires were distributed to the entire population, the population in this study was relatively small, as many as 59 students, the technique used was saturated sampling technique. Saturated sampling technique is a sampling technique in which each member of the population is sampled. This research uses multiple linear regression model. All data was processed using Microsoft Excel 2010 Software and Statistical Product And Service Solution (SPSS) release 22.0 for windows. The results of this study indicate that the self-efficacy variable has a partial positive effect on learning outcomes, this is evidenced by the obtained tcount > ttable or 2,665 > 2.0025. The variable utilization of learning facilities has a partial positive effect on learning outcomes, this is evidenced by the value of tcount greater than ttable or 8.719 > 2.0025. Self-efficacy and the use of learning facilities simultaneously have a positive effect on learning outcomes, this is evidenced by the value of Fcount greater than Ftable or 42.868 > 3.2 with the value of multiple linear regression equation Y = 33,442 + 0.187 X1 + 0.718 X2 + e. Based on the results of the research above, it can be concluded that self-efficacy and the use of learning facilities have a positive and significant effect on student learning outcomes.Keywords: Entrepreneurial Attitude, Social Support, Entrepreneurial Intention